Voices, memories and places: mapping the pioneers of Communication studies in Latin America - Pasian, Fernanda [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2024)
This paper looks at the scientific production of women in Communication studies in Latin America, especially in the first decades. The starting point is the research carried out by Berkin (2018), Heram e Gandara (2020, 2021) and Gobbi (2020, 2021, 2023), which deals, respectively, with silencing, the need to recognize them and the invisibility of these trajectories. The dynamics of gender inequalities show how the educational process of training communicators is an unequal communicational process. Initiatives that respond to this scenario are presented, followed by the proposal for a Map of Latin American Women Communication Researchers. It is understood that contact with a more diverse bibliography contributes to sustaining the theoretical and ethical commitments that professionals in the field of Communication build in their work practices.
Keywords: women in communication; Latin American studies; cartography